A sociocognitive approach to social problem solving in patients with traumatic brain injury: a pilot study. (2nd January 2019) - Saint-Jean, Mathilde; Allain, Philippe; Besnard, Jérémy
ABSTRACT: Primary objective : Patients with traumatic brain injury (TBI) have difficulty dealing with the social world and may display inappropriate social behavior that negatively affects their social and occupational rehabilitation. This difficulty may be explained by a social problem-solving (SPS) impairment, but little is yet known about the cognitive processes involved in the ability to solve social problems. Several publications have demonstrated that executive functions are related to social problem solving, but the role of social cognition needs to be confirmed. The present pilot study examined the expected relationships between SPS ability and both social cognition and social behavioral skills. Research design : We compared the performances of 15 patients with TBI on SPS, theory-of-mind and social behavior tasks with those of 25 matched healthy controls. Main outcomes and results : Our results showed for the first time that impaired social problem solving is associated with a theory-of-mind deficit, but surprisingly not with executive impairment. There was no evidence that SPS deficits predict social behavioral disorders. Conclusions : Studying social problem solving in patients with TBI may inform the design of more appropriate methods of social rehabilitation.